Evaluations of Clinical Utilization of Metagenomic Next-Generation Sequencing in Adults With Fever of Unknown Origin - Fu, Zhang-fan; Zhang, Hao-cheng; Zhang, Yi; Cui, Peng; Zhou, Yang; Wang, Hong-yu; Lin, Ke; Zhou, Xian; Wu, Jing; Wu, Hong-long; Zhang, Wen-hong; Ai, Jing-wen (Frontiers in Cellular and Infection Microbiology, 2022)
The diagnosis of infection-led fever of unknown origin (FUO) is still challenging, causing an difficulty for physicians to prescribe an early efficacious treatment, therefore, a novel pathogen detection platform is needed. Metagenomic next-generation sequencing (mNGS) is an unbiased approach for sequence-based identification of pathogens, but the study of the diagnostic values of mNGS in FUO is scarce. We conducted a retrospective cohort study to compare mNGS with culture or conventional methods including smear, serologic tests, and nucleic acid amplification testing in 175 FUO patients' clinical data were recorded and analyzed. The blood mNGS could increase the overall new organisms detection in infectious-led FUO by 22.9% and 19.79% in comparison of culture (22/96 vs 0/96; OR, ∞; P = 0.000), and conventional methods (19/96 vs 3/96; OR, 6.333; P = 0.001). Among which, bloodstream infection was the largest group of these identified, and the mNGS blood test could have a 38% improvement in the diagnosis rate compared to culture (19/50 vs 0/50; OR, ∞; P = 0.000) and 32.0% compared to conventional methods (16/50 vs 3/50; OR, 5.333; P = 0.004). Among the non-blood samples in infection-caused FUO, we observed that the overall diagnostic performance of mNGS in infectious disease was better than that of conventional methods by 20% (9/45 vs 2/45; OR, 4.5; P = 0.065)；And the use of non-blood mNGS in non-bloodstream infection increased the diagnostic rate by 26.2% (8/32 vs 0/32; OR, ∞; P = 0.008). According to 175 patients’ clinical decision-making, we found that the use of blood mNGS as the first-line investigation could increase 12.6% of diagnosis rate of FUO compared to culture, and the mNGS of other suspected parts as the second-line tests could further improve the diagnosis rate of other parts infection, by 29.2% in bloodstream infection and 44% in non-bloodstream infection. The application of mNGS in the FUO had significantly higher diagnostic efficacy than culture or other conventional methods. In FUO, the use of blood mNGS as the first-line investigation and samples from other suspected infection sites as the second-line test could enhance the FUO diagnosis and serve as a promising diagnostic protocol.